An integrated configuration with robust interfacial contact for durable and flexible zinc ion batteries. (August 2020) - Chen, Penghui; Zhou, Weiya; Xiao, Zhuojian; Li, Shaoqing; Wang, Zibo; Wang, Yanchun; Xie, Sishen
Abstract: The flexible zinc ion battery (ZIB) is deemed to be a promising candidate for flexible power supply due to its high security and low cost. However, conventional segregated battery configuration inevitably suffers from the relative displacement or detachment between two neighboring components at bending strain, which seriously degrade the performance of a flexible battery. Moreover, stubborn Zn dendrite drastically shortens the cycle life. Herein, by integrating Zn anode, zinc protective coating, polyamide separator and cathode into a single matrix, referred as the integrated electrode, a long cycle life and robust flexibility for ZIB in aqueous electrolyte are achieved. Seamless connection with the adjacent layers not only avoids the relative displacement or detachment caused by bending strain, but enhances the interfacial contact to promote the electrochemical kinetics. The built-in protective coating in the integrated configuration significantly inhibits the dendrites and side reactions for extending the durability. Furthermore, the integrated configuration makes the whole battery lighter, thinner and more powerful. Therefore, this work provides a new design idea for engineering innovative battery configuration and enables high performances for a flexible ZIB. Meanwhile, the research results would deliver great potential applications in flexible electronics and boost the development of configuration of energy storage devices. Graphical abstract: An ingenious configuration with robust interfacial contact is developed via the integration of Zn anode, zinc protective coating, polyamide separator and cathode into a single matrix, enabling the high flexibility and the dendrite-free boosted durability for zinc ion batteries. Image 1 Highlights: A flexible and durable zinc ion battery with integrated configuration is developed by manageable and scaleable process. Continuous seamless connection prevents the displacement or detachment and ensures the steady electron transfer. The built-in Zn anode protective coating inhibits dendrite growth and tightly glues the anode and polyamide separator. The integrated configuration delivers significantly prolonged lifespan, reduced overpotential and boosted flexibility.